PENGARUH WELAS ASIH DIRI (SELF COMPASSION) TERHADAP DEPRESI NARAPIDANA KASUS KEKERASAN SEKSUAL PADA LAPAS KELAS IIB TASIKMALAYA - Juliana, Rizki; Wibowo, Padmono (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The rise of acts of violence against prisoners in cases of sexual violence in correctional institutions plus the mental pressure received by prisoners makes many prisoners with cases of sexual violence experience depression. Self-compassion is considered a capability to reduce prisoner depression. This research aims to find out the influence of self-compassion in reducing the depression of prisoners in cases of sexual violence. This research uses the quantitative research methods which is the primary data that comes from a questionnaire filled out by 50 prisoners in cases of sexual violence at the Class IIB Tasikmalaya Penitentiary. The data analysis technique in this research uses normality tests, simple linear regression, significance, and determination. The analysis results obtained a strong negative influence of self-compassion on depression in prisoners committing sexual violence cases at the Class IIB Tasikmalaya Penitentiary. The higher the self-compassion, the lower the prisoner's depression. Keywords: Self-Compassion; Prisoner Depression; Tasikmalaya Penitentiary